Fully automated simultaneous peripheral arteriovenous exchange transfusion not seen to aggravate brain function and the disorder of the internal environment in neonates with severe hyperbilirubinemia - Wei-neng Lu; Xiao-yuan Yang; Shu-yao Ning; Zhuang-gui Chen; Si-nian Pan (Elsevier, 2021)
Background: The acute changes in brain function in newborn infants undergoing ET remain unclear. This study aimed to determine whether fully automated simultaneous peripheral arteriovenous ET would influence the brain function. Methods: A retrospective analysis was conducted on the clinical data of 39 neonates with hyperbilirubinemia who received ET. Seventeen patients were in the encephalopathy group, and the other 22 patients were in the non-encephalopathy group. Changes in amplitude-integrated electroencephalogram (aEEG) during ETs were analyzed, including background activities, sleep-wake cycling (SWC), and seizures. Before and after the ET, routine blood test parameters, electrolytes, blood glucose, and blood gas parameters were measured. Results: After ETs, there were no significant changes in the levels of pH, PaO2, PaCO2, lactate, and red blood cells, while the levels of total bilirubin, indirect bilirubin, blood potassium, blood sodium, serum calcium, while blood cells, and platelets were significantly lower and the level of blood glucose was significantly higher compared to those before therapy. There was no significant difference in the changes of electroencephalographic activities during ETs, including background activities, SWC, and seizures. However, there were significant differences in suppressions on background activities, while there were no significant statistical differences in SWC or seizures between the 2 groups. Conclusion: Fully automated simultaneous peripheral arteriovenous ET is safe and efficient without significant influence on the disorder of the internal environment and electroencephalographic activities after ET in neonates. However, background activities are more significantly depressed in infants of bilirubin encephalopathy than infants of non-encephalopathy during ET.